Design of a high-efficiency electrolytic energy conversion system based on equilibrium analysis of electric-field and flow-field through simulation and experiments. (1st February 2023) - Zhang, Pan; Wang, Jin; Shu, Yirui; Fu, Wenjun; Wang, Ye; Ye, Jinghua; Yang, Lin
Highlight: A novel high-efficiency electrolytic energy conversion system is proposed. Elucidate electrolyzer structure, distribution of electric field and flow field. Corrosion experiments are carried out to verify the simulation results. Key solutions for improving the performance of electrolyzers are obtained. Innovative approaches are proposed for building fluoride production lines. Abstract: In the context of sudden changes in global energy supply patterns, promoting the diversification of energy supply is an important movement for the sustainable development of the economy. Nuclear energy as a green and clean energy source has undergone rapid development. About 60 wt% of the world's fluorine production is used to produce uranium, a fuel for nuclear power plants. However, fluorine as a necessary raw material facing the challenges of high energy consumption and short lifespan of the electrolysis system. To overcome these drawbacks, this study aims to develop a high-efficiency electrolytic energy conversion system. Therefore, to optimize the design of the electrolysis system, the relationships between the electric field, the flow field and the electrode/electrolyzer geometry are simulated. Then, the simulation results are verified and further corrected by corrosion experiments. Subsequently, the key factors affecting the performance of the electrolyzer are obtained from the bubble separation experiment and simulation. Finally, a high-efficient electrolysis system is established and successfully put into industrial operation. In conclusion, in the course of model calculations, the method of reducing energy consumption is put forward, and the energy consumption is reduced from 17, 000 to 14, 980 kWh/ton by actual production, and the service life of carbon anode is extended from 90 days to 243 days. The breakthrough in fluorine electrolysis provides practical guidance for improving the performance of the electrolysis process.